2021
DOI: 10.46717/igj.54.1b.6ms-2021-02-24
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxides and Physiochemical Properties of Agricultural Soil on Bioaccumulation of Toxic Heavy Elements in Wheat Grains in Yaychi, Northeast of Iraq

Abstract: To investigate the potential link between toxic heavy elements in soil with soil physiochemical properties and oxides, as well as their impact on the bioaccumulation of these elements in wheat grains. Agriculture soil and wheat grains were sampled from Yaychi area, Kirkuk northeast of Iraq. Soil physiochemical properties, oxides and toxic heavy elements contents were determined. The average concentration of toxic heavy elements in soil was in this order Ni> Cr> Pb> As> Cd> Hg, and some of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…It is also observed that the element concentration in all the studied samples is less than the two selected standard samples they are surface (SA6) is 130.44ppm and the subsurface (SbA6) is 132.59ppm. It may be related to the high application of fertilizers and herbicides in agriculture, which is an important source of nickel in the soil (Chauhan et al, 2008;Yasmeen et al 2010;Al-Jumaily and Hasseb, 2021). Or it is a result of the sulfur rich geological formations , such as the Fatha Formation exposed in the study area which contain gypsum quarries in the region, nickel exhibits high geochemical affinity with sulfur under reduce conditions, and the element is concentrated in rich organic contain clays and precipitates as sulfide (Rankama and Sahama, 1950;Butu, 2013).…”
Section: Heavy Elements Geochemistry In the Soil Of The Study Areamentioning
confidence: 99%
“…It is also observed that the element concentration in all the studied samples is less than the two selected standard samples they are surface (SA6) is 130.44ppm and the subsurface (SbA6) is 132.59ppm. It may be related to the high application of fertilizers and herbicides in agriculture, which is an important source of nickel in the soil (Chauhan et al, 2008;Yasmeen et al 2010;Al-Jumaily and Hasseb, 2021). Or it is a result of the sulfur rich geological formations , such as the Fatha Formation exposed in the study area which contain gypsum quarries in the region, nickel exhibits high geochemical affinity with sulfur under reduce conditions, and the element is concentrated in rich organic contain clays and precipitates as sulfide (Rankama and Sahama, 1950;Butu, 2013).…”
Section: Heavy Elements Geochemistry In the Soil Of The Study Areamentioning
confidence: 99%